SYSTEMATIC LITERATURE REVIEW : TRENDS IN E-LKPD IN THE CONTEXT OF SCIENCE LEARNING - Ni Ketut Widiantari; I Wayan Redhana; I Nyoman Tika; I Wayan Subagia; I Wayan Suja (Adisam Publisher, 2025)
Technological developments demand various sustainable innovations in the world of education. E-LKPD is one of the relevant media to support the learning process. This research is a systematic literature review (SLR) that aims to analyze the trend of E-LKPD in the context of science learning. This study is carried out by identifying, analyzing, and synthesizing research articles published in the last five years from 2020 to 2025 from leading databases such as Scopus, Google Scholar, and DOAJ. The results of the analysis show that the trend of using E-LKPD in science learning has increased significantly, especially in the development of interactive features, multimedia integration, and the application of innovative learning models such as inquiry, discovery learning, PBL, and PJBL. The results were obtained from 38 inclusive articles, after going through a filtering stage, 20 articles were used. The inclusive E-LKPD plays an important role in improving learning motivation, learning outcomes, scientific literacy, critical thinking skills, collaboration skills, and science process skills. However, challenges related to the technical, pedagogical, and cultural aspects of E-LKPD still need to be considered.